Recovery and confirmation of Haemonchus contortus from abomasal contents of roe deer (Capreolus capreolus) in Eastern-Hungary (Biharugra): A diagnostic case study - Khangembam, Rojesh; Tóth, Mariann; Gulyas, Gabriella; Czeglédi, Levente; Vass, Nóra (Acta Agraria Debreceniensis, 2023)
Gastrointestinal parasites are ubiquitous. They occur both in wild and domesticated animals. Among such parasites of veterinary importance is the trichostrongyle worms, out of which the Haemonchus contortus species is regarded as the most pathogenic one in the small ruminant industry. The occurrence of this parasite in the sheep flock is now very well documented and an established fact in Europe, although the parasite was original of the warmer climatic region. Studies on the cross-transmission of H. contortus between the wild and domesticated animals are also on the rise although the question of the direction of transmission is still debated. This is an important area that needs to be addressed as it could potentially contribute indirectly to mitigating anthelmintic resistance. Hungary also has reported its share of the occurrence of the parasite, mainly in the sheep flock and a certain population of roe deer. The study presented here is the preliminary results of a diagnostic case study that confirms the presence of H. contortus in wild ruminant deer species that are close to the domesticated sheep population.